A Numerical Study on Turbulent Couette Flow and Heat Transfer in Concentric Annuli by Means of Reynolds Stress Turbulence Model - Shuichi Torii; Wen-Jei Yang (International Journal of Rotating Machinery)
A numerical study is performed to investigate fluid flow and heat transfer characteristics in a concentric annulus with a slightly heated inner core moving in the flow direction and a stationary, insulated outer cylinder. Emphasis is placed on the effect of inner core movement on the flow structures, i.e. the normal components of the Reynolds stress and its off-diagonal one. A Reynolds stress turbulence model is employed to obtain these turbulence quantities. The governing boundary-layer equations are discretized by means of a control volume finite-difference technique and numerically solved using the marching procedure. It is found from the study that (i) the streamwise movement of the inner core causes an attenuation in the normal Reynolds stresses, although the inherent anisotropy is maintained and the appreciable turbulence remains, (ii) the Reynolds stress in the inner wall region is substantially diminished due to the inner core movement, resulting in a decrease in the heat transfer performance, and (iii) an increase in the velocity ratio of the moving inner core of the fluid flow induces a decrease in the Nusselt number as well as the Reynolds stress in the region near the inner core.